A Bibliometric Analysis of Macrophage Research Associated with Periodontitis Over the Past Two Decades - Yu Qiu; Zhenzhen Ding; Deqin Yang (International Dental Journal)
Macrophages are vital for regulating periodontal health, and numerous studies have extensively investigated their role in periodontitis progression. This study employs bibliometric analysis to identify research trends and hotspots related to macrophages in periodontitis from 2004 to 2024, thereby guiding future investigations and exploring potential clinical applications. Literature retrieval and dataset export were conducted via the Web of Science Core Collection database. Subsequently, bibliometric analysis was performed and the results were visualized using Microsoft Office Excel, VOSviewer, CiteSpace, and GraphPad Prism. A total of 1542 papers from 2004 to 2024 on the macrophages associated with periodontitis were identified. The annual number of publications and citations has steadily increased. China and the United States were the primary collaborators and drivers of research. Sichuan University had the largest number of published studies. The Journal of Periodontal Research published the most papers, while the Journal of Periodontology had the most citations. Daniel Grenier was the most prolific author and George Hajishengallis was the most frequently co-cited author. Co-citation analysis indicated that researchers primarily investigate the mechanisms of macrophages in periodontitis through both in vivo and in vitro experiments. Emerging research hotspots encompass keywords such as “macrophage polarization,” “extracellular vesicles,” and “regeneration.” Research on macrophages in periodontitis is progressing quickly, and their strategic targeting offers a new and promising direction for future studies on regenerating periodontal tissues. The utilization of extracellular vesicles derived from diverse sources to regulate M1/M2 macrophage polarization presents a promising strategy for the treatment of periodontitis.